Aggregatibacter actinomycetemcomitans (Aa) Under the Radar: Myths and Misunderstandings of Aa and Its Role in Aggressive Periodontitis - Fine, Daniel H.; Patil, Amey G.; Velusamy, Senthil K. (Frontiers in Immunology, 2019)
Aggregatibacter actinomycetemcomitans (Aa) is a low-abundance Gram-negative oral pathobiont that is highly associated with a silent but aggressive orphan disease that results in periodontitis and tooth loss in adolescents of African heritage. For the most part Aa conducts its business by utilizing strategies allowing it to conceal itself below the radar of the host mucosal immune defense system. A great deal of misinformation has been conveyed with respect to Aa biology in health and disease. The purpose of this review is to present misconceptions about Aa and the strategies that it uses to colonize, survive, and evade the host. In the process Aa manages to undermine host mucosal defenses and contribute to disease initiation. This review will present clinical observational, molecular, and interventional studies that illustrate genetic, phenotypic, and biogeographical tactics that have been recently clarified and demonstrate how Aa survives and suppresses host mucosal defenses to take part in disease pathogenesis. At one point in time Aa was considered to be the causative agent of Localized Aggressive Periodontitis. Currently, it is most accurate to look at Aa as a community activist and necessary partner of a pathogenic consortium that suppresses the initial host response so as to encourage overgrowth of its partners. The data for Aa's activist role stems from molecular genetic studies complemented by experimental animal investigations that demonstrate how Aa establishes a habitat (housing), nutritional sustenance in that habitat (food), and biogeographical mobilization and/or relocation from its initial habitat (transportation). In this manner Aa can transfer to a protected but vulnerable domain (pocket or sulcus) where its community activism is most useful. Aa's “strategy” includes obtaining housing, food, and transportation at no cost to its partners challenging the economic theory that “there ain't no such thing as a free lunch.” This “strategy” illustrates how co-evolution can promote Aa's survival, on one hand, and overgrowth of community members, on the other, which can result in local host dysbiosis and susceptibility to infection.